One year of continuous measurements of soil CH4 and CO2 fluxes in a Japanese cypress forest: Temporal and spatial variations associated with Asian monsoon rainfall. Issue 4 (14th April 2015) - Sakabe, Ayaka; Kosugi, Yoshiko; Takahashi, Kenshi; Itoh, Masayuki; Kanazawa, Akito; Makita, Naoki; Ataka, Mioko
Abstract We examined the effects of Asian monsoon rainfall on CH4 absorption of water‐unsaturated forest soil. We conducted a 1 year continuous measurement of soil CH4 and CO2 fluxes with automated chamber systems in three plots with different soil characteristics and water content to investigate how temporal variations in CH4 fluxes vary with the soil environment. CH4 absorption was reduced by the "Baiu" summer rainfall event and peaked during the subsequent hot, dry period. Although CH4 absorption and CO2 emission typically increased as soil temperature increased, the temperature dependence of CH4 varied more than that of CO2, possibly due to the changing balance of activities between methanotrophs and methanogens occurring over a wide temperature range, which was strongly affected by soil water content. In short time intervals (30 min), the responses of CH4 and CO2 fluxes to rainfall were different for each plot. In a dry soil plot with a thick humus layer, both fluxes decreased abruptly at the peak of rainfall intensity. After rainfall, CO2 emission increased quickly, while CH4 absorption increased gradually. Release of accumulated CO2 underground and restriction and recovery of CH4 and CO2 exchange between soil and air determined flux responses to rainfall. In a wet soil plot and a dry soil plot with a thinner humus layer, abrupt decreases in CH4 fluxes were not observed. Consequently, the Asian monsoon rainfall strongly influenced temporal variations in CH4 fluxes, and the differences in flux responses to environmental factors among plots caused large variability in annual budgets of CH4 fluxes.